2016
DOI: 10.4103/1735-5362.189301
|View full text |Cite
|
Sign up to set email alerts
|

The effect of adenosine A1 receptor agonist and antagonist on p53 and caspase 3, 8, and 9 expression and apoptosis rate in MCF-7 breast cancer cell line

Abstract: Adenosine receptor family especially A1 type is expressed in breast cancer cells in which P53 and caspase genes are wild-type. The aim of this study was to investigate the correlation between A1 receptor and either cell apoptosis or proliferation and also to recognize the relationship between this receptor and P53 and the expression of caspases 3, 8 and 9 in MCF-7 cell line. MCF-7 cells were treated intermittently with A1 receptor agonist N6-Cyclopentyladenosine (CPA) and A1 receptor antagonist 1,3-dipropyl-8-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…P53 is a tumor suppressor protein regulating cell cycle progression and apoptosis in tumor cells (Bordon, ; Maiuri et al, ). In line with this, Dastjerdi, Rarani, Valiani, and Mahmoudieh ( ) showed that upon addition of N6‐Cyclopentyladenosine (CPA), an A1 adenosine receptor agonist, viability rate of MCF‐7 cells increases and apoptosis reduces dramatically. Expression of P53 and caspases decrease as well.…”
Section: Role Of Adenosine In Apoptosis In Breast Cancermentioning
confidence: 73%
“…P53 is a tumor suppressor protein regulating cell cycle progression and apoptosis in tumor cells (Bordon, ; Maiuri et al, ). In line with this, Dastjerdi, Rarani, Valiani, and Mahmoudieh ( ) showed that upon addition of N6‐Cyclopentyladenosine (CPA), an A1 adenosine receptor agonist, viability rate of MCF‐7 cells increases and apoptosis reduces dramatically. Expression of P53 and caspases decrease as well.…”
Section: Role Of Adenosine In Apoptosis In Breast Cancermentioning
confidence: 73%
“…It has been demonstrated that the occurrence of tumor development depends on the dynamic balance between cell proliferation and apoptosis (23). Caspase-3 is a important apoptotic protein for various cells, and caspase-3 activation can induce apoptosis in cancer cells (24). The Bcl-2 family of apoptosis-related proteins includes important regulatory factors: Bcl-2 inhibits apoptosis, whereas Bax and Bak promote apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…These processes are likely to be related to PRODH/POX-dependent ROS signaling and subsequent activation of caspases or regulation by transcription factors. MCF-7 cells express wild-type p53 protein [ 28 ]. PRODH/POX expression is regulated by P53 [ 29 31 ], while PRODH/POX down regulates HIF-1α signaling [ 32 ], that mediate glycolysis, angiogenesis, metastasis and survival [ 15 ].…”
Section: Introductionmentioning
confidence: 99%